2007
DOI: 10.1539/joh.49.376
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Agreement between Weight Perception and Body Mass Index of Japanese Workers: MY Health Up Study

Abstract: Degree of Agreement between WeightPerception and Body Mass Index of Japanese Workers: MY Health Up Study: Mariko INOUE, et al. Department of Public Health, Graduate School of Medicine, University of Tokyo-The objective of this study was to assess the degree of agreement between body mass index (BMI) and weight perception of Japanese office workers between the ages of 20 and 65. We sent 43,064 self-administered health-related questionnaires to all employees of a financial firm in Japan in October 2004. The ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 31 publications
(28 reference statements)
9
35
2
Order By: Relevance
“…Secondly, if students perceive themselves as obese or overweight they are less likely to be of healthy weight and more likely to be overweight. These results are in line with prior studies conducted in Iran [3], in the United States [31], in Western Europe [32,33], and in Asian countries such as Japan [34], Korea [35] and China [36]. From the viewpoint of the authors on the base of the results of the present study one of the possible reasons for these outcomes can be that the males are more concerned about their health and so they have lesser tendencies to be overweight.…”
Section: Resultssupporting
confidence: 92%
“…Secondly, if students perceive themselves as obese or overweight they are less likely to be of healthy weight and more likely to be overweight. These results are in line with prior studies conducted in Iran [3], in the United States [31], in Western Europe [32,33], and in Asian countries such as Japan [34], Korea [35] and China [36]. From the viewpoint of the authors on the base of the results of the present study one of the possible reasons for these outcomes can be that the males are more concerned about their health and so they have lesser tendencies to be overweight.…”
Section: Resultssupporting
confidence: 92%
“…In this study, 20.0% and 23.9% of men with prehypertension, and 23.9% and 36.1% of women with prehypertension were upper normal weight (BMI, 23.5-24.9 kg/m 2 ) and overweight (BMI, ≥ 25 kg/m 2 ), respectively. Among Japanese workers, 31.2% of men and 19.5% of women are overweight or obese (Inoue et al 2007). Moreover, these prevalences are expected to increase in Japan in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on ideal body weight and body image have focused on children or adolescent females 8,9) , but few of these studies have addressed male workers. Few studies have focused on BMI and on weight self-perception in the working population 10,11) , and our review of the literature found none that examined the relationship between weight perception and lifestyle habits. We investigated weight self-perceptions and health-related behaviors of male Japanese bus drivers and described the impact of weight perception and lifestyle on their physical condition and health problems.…”
Section: Introductionmentioning
confidence: 98%